Glossary of European Union Internal Market terminology. Amended to include the Association Agreement between the European Union and Ukraine - Пашковський, Микола Іванович; Пашковский, Николай Иванович; Pashkovskyi, Mykola I.; Барський, Вадим Рудольфович; Барский, Вадим Рудольфович; Barskyi, Vadym R.; Кацин, Михайло Юрійович; Кацин, Михаил Юрьевич; Katsyn, Mikhail Yu.; Алєксєєва, Ірина Михайлівна; Алексеева, Ирина Михайловна; Alieksieieva, Iryna M.; et al. (Odesa : Feniks, 2016)
This Glossary contains more than 400 terms used within the EU Internal Market. This text was compiled in accordance with the European Union-Ukraine Association Agreement.
Глосарій термінів внутрішнього ринку Європейського Союзу доповнений відповідно до угоди про асоціацію між Європейським Союзом і Україною
Glossary of European Union Internal Market terminology. Amended to include the Association Agreement between the European Union and Ukraine [Electronic resource] / сompilers: Tuliakov V.O. (Editor), Pashkovskyi M.I., Barskyy V.R. (Technical editor), Katsyn M.Y., Alekseeva I.M. – Odesa: Feniks, 2016. – 216 с. – Access mode: http://iele.bazick.com/books/289-glossary-ofeu- internal-market-terminology
Keywords: Glossary; European Union; Internal Market; глоссарій; Європейський Союз; внутрішній ринок; глоссарий; Европейский Союз; внутренний рынок